Impact on the Properties of Asphalt and an MDC – 1 Asphalt Mix When Adding SBR - Reyes, Fredy (2025)
As is well known, the use of polymers in the preparation of asphalt mixtures dates back more than half a century. In countries with more advanced technology, laboratory tests are conducted related to the behavior of polymer-modified asphalt mixtures. Projects are developed to improve pavement performance, resulting in significantly longer design periods and service life compared to conventional pavements.